48-Hour Effects of Monitored Cooperative High-Intensity Interval Training on Adolescent Cognitive Functioning. Issue 2 (April 2019) - Mezcua-Hidalgo, Alberto; Ruiz-Ariza, Alberto; Suárez-Manzano, Sara; Martínez-López, Emilio J.
Physical activity has been positively related to better cognitive performance though the effects of varied exercise type and intensity and the duration of cognitive benefits are unclear. This study analyzed the effect of 16 minutes of monitored cooperative high-intensity interval training (monitored C-HIIT) at the start of the school day, on various cognitive variables over the next 24–48 hours. We randomly assigned 158 participants either to a control group ( n  = 81) that engaged only in static stretching or to an experimental group ( n  = 77) that performed monitored C-HIIT. We assessed cognitive functioning before the exercise, immediately afterward, and for five follow-up time points over the next two days (i.e., at 2, 3, 4, 24, and 48 hours). We analyzed age, sex, body mass index, and moderate-to-vigorous physical activity as potential confounder variables. Adolescents in the monitored C-HIIT group increased selective attention by 17.39% during the next hour ( p  = .015) and increased concentration by 20.31% and 15.26% during the first ( p  = .022) and second ( p  = .059) subsequent hours, respectively. This positive short-term benefit of monitored C-HIIT during immediate subsequent hours is an important finding with implications for the school curricula and schedule.